INSTANTANEOUS DEATH DUE TO ISOLATED SCROTAL TRAUMA (Journal of Forensic Medicine & Toxicology, 2020)
Instantaneous death refers mortality within extremely short time after injury or seizure otherwise. Death is so contemporaneous and even without miniscule chance of recovery after injury. This is in contrast to immediate death where injured survives brief period1. Sudden death as per ICD-10 is non-violent and un-explained death within 24 hours from onset of symptoms2. Violence is out in all instantaneous, immediate and sudden deaths. Instantaneous deaths are seen in hypertrophic cardiomyopathy, electrical disturbance of heart, brain aneurysm, aortic dissection and embolism. Inherent mobility along with presence of cremasteric reflex and tunica albuginea with additional buffering by dartos muscle in scrotum protects testes against injuries in spite of being potentially exposed organs3. Testicular arteries with collaterals are long, tortuous with direct origin and in continuity from high pressure abdominal aorta. This rich blood supply sustains viability of these precious organs of generation even during compromised states.
Keywords: Young adult; embolism; blood